Implementasi Peraturan Bupati Aceh Tengah Nomor 14 Tahun 2018 Tentang Penurunan Stunting Melalui Edukasi Kesehatan Ibu Dan Calon Ibu Di Desa Wih Sagi Indah - Efendi, Muhsin; Pathonah, Nurul; Nisa, Siti Umairah (Universitas Gajah Putih, Indonesia, 2023)
Stunting is the failure of a child to grow and develop optimally due to the impact of cumulative and continuous malnutrition. Or chronic nutritional problems where families and communities do not yet feel that this is a problem, this is because not many people know the causes, impacts and prevention. The central and regional governments are jointly trying to overcome this problem. The Regional Government of Central Aceh Regency is also trying to resolve this problem with the various policies it has adopted. Gajah Putih University's Thematic Real Work Lecture (KKNT) which is placed in Wih Sagi Indah Village, Silih Nara District, Central Aceh Regency tries to take part in preventing the problem of stunting through the implementation of Central Aceh Regent's regulation Number 14 of 2018 through Health Education for Mothers and Prospective Mothers as an effort to Prevent Stunting Problems in Wih Sagi Indah Village, Silih Nara District, Central Aceh Regency, aimed at mothers who have toddlers and mothers who are pregnant. It is hoped that with this activity the public's understanding of health can increase and stunting sufferers can decrease, so that the desire to create a healthy, intelligent and superior society can be achieved.